Iceland : Selected Issues Paper. (IMF Staff Country Reports; Country Report, 2015)
This Selected Issues paper examines implications of capital account liberalization in Iceland. Capital controls were critical in 2008 to avoid a more severe collapse of the Icelandic economy. Six years later, capital inflows have been liberalized, but most outflows remain restricted. Iceland has used the breathing room to reduce flow and stock vulnerabilities, strengthen institutions, and prepare for the lifting of capital controls. Simulations using the central bank's Quarterly Macroeconomic Model (QMM) suggest that, compared with the 2008 crisis episode, the economy can better withstand the impact of an abrupt removal of capital controls. However, the outcome would be dependent on a number of factors, including resident depositor behavior.